2006
DOI: 10.1021/es051804n
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Uranium(VI) Reduction by Hydrogen Sulfide in Anoxic Aqueous Systems

Abstract: Aqueous U(VI) reduction by hydrogen sulfide was investigated by batch experiments and speciation modeling; product analysis by transmission electron microscopy (TEM) was also performed. The molar ratio of U(VI) reduced to sulfide consumed, and the TEM result suggested that the reaction stoichiometry could be best represented by UO2(2+) + HS- = UO2+ S* + H+. At pH 6.89 and total carbonate concentration ([CO32-]T) of 4.0 mM, the reaction took place according to the following kinetics: -d[U(VI)]/dt = 0.0103[U(VI)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
135
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(146 citation statements)
references
References 30 publications
11
135
0
Order By: Relevance
“…Aqueous sulfide U(VI) reduction experiments were conducted in duplicate using serum bottles with butyl rubber septa and anoxic solutions as previously described (38). All bottles and solutions were thoroughly purged with ultra high purity He before initiation of the experiments to remove O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Aqueous sulfide U(VI) reduction experiments were conducted in duplicate using serum bottles with butyl rubber septa and anoxic solutions as previously described (38). All bottles and solutions were thoroughly purged with ultra high purity He before initiation of the experiments to remove O 2 .…”
Section: Methodsmentioning
confidence: 99%
“…[22,23] Uranium can also be reduced by precipitated or biogenically produced Fe-sulfide and by aqueous sulfide under anoxic conditions. [15,[24][25][26][27] Enzymatic reduction of U VI has been observed by iron and sulfate reducing bacteria. [28,29] Although both As III and As V can be adsorbed to iron minerals, As can be released, not only by desorption, but by microbial reduction of iron mineral phases, resulting in mineral dissolution.…”
Section: Introductionmentioning
confidence: 99%
“…The solubility of tetravalent uranium species is lower by several orders of magnitude and usually controlled by uraninite (UO 2 ). In anoxic aqueous systems, reduction of U(VI) to UO 2 can occur either chemically, e.g., by hydrogen sulfide (Hua et al 2006), by surface catalyzed reactions involving coadsorption of Fe(II) and U(VI) on iron(III) oxides (Behrends and Van Cappellen 2005;Fredrickson et al 2000;Jeon et al 2005), or microbially, i.e., catalyzed by enzymes.…”
Section: Introductionmentioning
confidence: 99%
“…While the above investigations were carried out at neutral pH and fixed carbonate concentrations, two additional studies demonstrated the inhibition of U(VI) bioreduction by dissolved inorganic carbon (DIC). Investigating the kinetics of abiotic U(VI) reduction by hydrogen sulfide in anoxic aqueous systems, Hua et al (2006) reported that the reduction was almost completely inhibited at the following conditions: [DIC] ≄ 15 mM at pH 6.89, [DIC] ≄ 4 mM at pH 8.01, and [DIC] ≄ 2 mM at pH 9.06. These combinations of DIC concentrations and pH suggest an anti-correlation between the concentration of U(VI)-carbonate complexes and reduction rate.…”
Section: Introductionmentioning
confidence: 99%